Creating and caring for castrates - Reusch, Kathryn (Frontiers in Environmental Archaeology, 2025)
IntroductionHuman castration has a long history. Reasons for castration varied, but one continuous driver was the understanding that castration made individuals born with testes infertile. This manufactured infertility made castrates ideal guards in elite households, especially in cultures such as the Ottoman, Persian, and Chinese Empires. The retention of the childlike high voice, gave another reason for castration -the production of elite high-voiced singers for Catholic Church choirs.MethodsDocumentation related to the process of castration and medical studies of castrates were examined to determine what was known about the effects of castration, what medical treatment castrates received, and what modern doctors learned from castrates' bodies.ResultsThe production of castrates was an important process, one which was medically understood to different degrees in different places, causing high mortality rates in some areas and practically none in others. Cultures which used castrates noted certain physical characteristics and medical conditions, but little specific care was given to castrates' medical needs beyond their castration. As medicine became increasingly professionalized, doctors became interested in castrates. Several doctors examined groups of living castrates, while others examined their bodies to understand the processes of castration and why certain bodies exhibited the same effects even when they had not been castrated. These studies contributed to the birth of endocrinology, letting us understand not only of the effects of castration, but a range of hormonal conditions.DiscussionAs some castrates had been enslaved far away from their families and others had been disowned by their natal families, they frequently joined together to provide proper burial for each other. Others who were wealthy would endow monasteries to ensure their burial in their chosen manner, retiring to those establishments in their later years. Other castrates would retire to these to serve as caretakers and guards, understanding that they would be buried in the grounds. In this way, castrates created for themselves communities of care in both life and death. The medical knowledge provided by studying castrates has given the ability to treat some problems intersex people face, allowed trans individuals to safely transition, and created treatments for diseases such as prostate cancer. Thus, castration remains relevant today, and we see that castrates have contributed to wider aspects of public health in a way that many do not know or even acknowledge, while they rarely received this same level of care in return.